Introducing the Term DAGUSIBU (Get, Use, Save and Dispose) Medicine at Senior High School State 6 of Ternate - Ermalyanti Fiskia; Muhammad Fakhrur Rajih Hi Yusuf; Amran Nur (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Technological developments are increasingly rapid, and everything can be obtained easily by using a device to process transactions, one of which is in the health sector. The increase in sales of medicines and medical equipment through e-commerce illegally and without supervision, as well as health articles from unclear sources, has led to an increase in drug use errors. To ensure the safety of medicines consumed by the public, the Indonesian Pharmacists Association introduced the DAGUSIBU movement to monitor the use and management of medicines by the community, especially in rural areas with limited health facilities. Through this movement, the team of lecturers and students from the Pharmacy Study Program, Faculty of Medicine, Khairun University, carried out service activities with the theme of socialization and education related to DAGUSIBU at Senior High School State 6 of Ternate. The activities were carried out through interactive lecture and discussion methods and were equipped with pre and post-tests. Based on the evaluation results, it can be concluded that there is an increase in knowledge of up to 80% after providing material which was previously only 30%.